NEW ARCHAEOBOTANICAL DATA REGARDING THE DIET OF THE GAVA CULTURE COMMUNITIES FROM THE FORTIFIED SETTLEMENT OF TELEAC (ALBA COUNTY) ROMANIA - Beatrice Ciuta (Journal of Ancient History and Archaeology, 2022)
The aim of this study is to present new archaeobotanical data regarding the charred macro remains recovered during 2018 archaeological campaign from the famous hillfort Teleac  (Alba county, Romania) belonging to Gava culture. The most important evidences of macro remains were recovered from inside of a burnt house from Trench 6 and few pits around it. The archaeological site belonging the Late Bronze Age has offered has provided in last year’s very important data regarding the plant species used in the diet of communities which inhabited the hillfort from Teleac